The safety window of blood magnesium in pulmonary complications of non-pulmonary sepsis: A U-shaped risk and prognostic analysis based on MIMIC-IV - Taotao Peng; Yu Li; Yukun Ren; Mi Yang; Zonghong Long; Dukun Zuo; Lu Huang; Huawei Liu; Zhenxin Duan; Hong Li (PLoS ONE, 2026)
Pulmonary complications in non-pulmonary sepsis (PC-NPS) are the leading cause of morbidity and mortality in the intensive care unit. Early prevention and monitoring are paramount since the prevention strategies remain limited yet. Magnesium, an essential electrolyte involved in inflammation and vascular regulation, may influence the development of such complications. This retrospective cohort study used data from the MIMIC-IV database to explore the relationship between baseline serum magnesium levels and PC-NPS among 4,836 patients with non-pulmonary sepsis. Survival analysis demonstrated that patients who developed PC-NPS had significantly higher 90-day mortality compared with those without lung injury. When stratified by baseline serum magnesium quartiles, patients in the highest quartile (>2.1 mg/dL) showed the poorest survival. Multivariable logistic regression confirmed that elevated magnesium was independently associated with increased risk of PC-NPS, and restricted cubic spline modeling revealed a U-shaped, nonlinear association between baseline magnesium concentration and PC-NPS risk. Inflection points at 1.26 and 1.91 mg/dL identified a range of relatively lower risk. These findings suggest that baseline serum magnesium levels exhibit a U-shaped relationship with the risk of PC-NPS. Evaluating these levels may aid in clinical prognostication and the exploration of underlying mechanisms.